A brief eHealth tool delivered in primary care to help parents prevent childhood obesity: a randomized controlled trial. Issue 11 (10th November 2016) - Byrne, J. L. S.; Cameron Wild, T.; Maximova, K.; Browne, N. E.; Holt, N. L.; Cave, A. J.; Martz, P.; Ellendt, C.; Ball, G. D. C.
Summary: Objectives: To determine the feasibility and preliminary impact of an electronic health (eHealth) screening, brief intervention and referral to treatment (SBIRT) delivered in primary care to help parents prevent childhood obesity. Methods: Parents of children (5–17 years) were recruited from a primary care clinic. Children's measured height and weight were entered into the SBIRT on a study‐designated tablet. The SBIRT screened for children's weight status, block randomized parents to one of four brief interventions or an eHealth control and provided parents with a menu of optional obesity prevention resources. Feasibility was determined by parents' interest in, and uptake of, the SBIRT. Preliminary impact was based on parents' concern about children's weight status and intention to change lifestyle behaviours post‐SBIRT. Results: Parents ( n  = 226) of children (9.9 ± 3.4 years) were primarily biological mothers (87.6%) and Caucasian (70.4%). The proportion of participants recruited (84.3%) along with parents who selected optional resources within the SBIRT (85.8%) supported feasibility. Secondary outcomes did not vary across groups, but non‐Caucasian parents classified as inaccurate estimators of children's weight status reported higher levels of concern and intention to change post‐SBIRT. Conclusions: Our innovative, eHealth SBIRT was feasible in primary care and has the potential to encourage parents of unhealthy weight children towards preventative action.